1992
DOI: 10.1002/eqe.4290210505
|View full text |Cite
|
Sign up to set email alerts
|

Groundborne vibrations due to trains in tunnels

Abstract: SUMMARYAn analytical procedure is presented for determining groundborne vibrations in buildings due to subway trains. The procedure involves a finite element idealization of the subway-soil-structure interaction problem, using an analytical model for the train loading spectrum at the tunnel invert. Both direct fixation and floating slab track support systems ate considered. The train model is verified using the measurements of rail velocities. The proposed prooedure is applied to the case of a four-storey podi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The measurements presented in Bongini et al 36 demonstrate that irregularities up to at least 1 m wavelength can be measured repeatably with at least some systems that process axlebox accelerations. Chua et al 37 found reasonable correlation up to about 200 Hz of measured vibration levels on floating slab track in an underground system and those calculated assuming a spectrum of irregularities measured by British Rail. The spectrum is rather puzzling as it contains components that are a function not only of wavelength but also of velocity.…”
Section: Introductionmentioning
confidence: 82%
“…The measurements presented in Bongini et al 36 demonstrate that irregularities up to at least 1 m wavelength can be measured repeatably with at least some systems that process axlebox accelerations. Chua et al 37 found reasonable correlation up to about 200 Hz of measured vibration levels on floating slab track in an underground system and those calculated assuming a spectrum of irregularities measured by British Rail. The spectrum is rather puzzling as it contains components that are a function not only of wavelength but also of velocity.…”
Section: Introductionmentioning
confidence: 82%
“…Determining the vehicle response is important e.g. for the study of passenger comfort, stability of railway vehicles [199], risk of derailment, and loading of vehicle components, whereas the response of the supporting infrastructure is of interest for track and road design [160] and environmental problems of ground-borne vibration [18,19,20,22,23,24,26,27,29,30,211] and noise [16,21,212,213,214]. The focus of the study will determine the detail of modeling in both structures, as well as the kind of excitation mechanisms considered.…”
Section: Interaction Through a Moving Interfacementioning
confidence: 99%
“…Mathematical solutions have been developed by Garg and Wang (1985), Hino et al (1986), Honda et al (1986), Diana and Cheli (1989), Klasztorny and Langer (1990), Kuang-Han Chu et al (1992), and, recently, by Yang and Fonder, (1996). The bridge and the vehicle have been modeled by a finite element method, and the coupled equations have been solved by direct time integration.…”
Section: Introductionmentioning
confidence: 99%